Commuting Differential Operators of Rank 3 Associated to a Curve of Genus 2 - Zuo, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
In this paper, we construct some examples of commuting differential operators L₁ and L₂ with rational coefficients of rank 3 corresponding to a curve of genus 2.